Relationship of oocyte development with follicular sized and metabolites follicular fluid composition in local buffaloes - Al-Rubaei, Hashem M.; Al-Hissnawi, Mayada S.; Al-Nuaimi, Ali J. (Journal of Kerbala for Agricultural Sciences, 2017)
This project was designed to evaluate some metabolites composition of ovarian follicular fluid from different sized follicles and it's relationship with oocyte development. 120 ovaries were collected from 60 adults non-pregnant female's buffalo slaughtered at abattoirs of Babylon province during the period from September 2016 to February 2017 and transported to the laboratory within 2 hours post slaughter. The ovarian follicular fluid were aspirated from follicles for recovery and evaluation of oocytes and determination of metabolites composition. The oocytes were evaluated and the ovarian follicular fluid samples were analyzed for determinate the metabolites (glucose, total protein, total cholesterol and triglycerides). The results showed that the mean concentrations of glucose and total cholesterol in ovarian follicular fluid of large follicles were significantly higher (P<0.05) compared with small follicles, while the mean concentrations of total protein and triglycerides in ovarian follicular fluid of large follicles were significantly lower (P<0.05) compared with small follicles. The results of the present study also indicated that the percentage of the presence of oocytes with cumulus oophorus around oocyte was significantly higher (P<0.05) with increased of follicular size. The percentage of completely zona pellucida was significantly higher (P<0.05) with enlargement of follicular size. The average of oocyte diameter was significantly increased (P<0.05) with enlargement of follicular size. The percentage of completely hemogenous cytoplasm were significantly higher (P<0.05) with increased of follicular size. In conclusion, based on these data we can infer that the inferior oocyte quality inside of follicle may be cause to deteriorate infertility in female's buffalo. The oocytes growth and mature in metabolites composition of follicular fluid in fluctuate or variation considerably with changes in follicular size.